OPTIMALISASI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER DALAM PENGEMBANGKAN INFRASTRUKTUR PERUSAHAAN UNTUK MEMENANGKAN PERSAINGAN GLOBAL - Muhammad Yusuf; Apry Linda Diana (Jurnal Ekonomi, 2016)
Globalization in the business sector businesses opportunities to expand its market share and network his company, as well as the managerial concept of making customers as a top priority in winning the global competition make the new managerial patterns that develop in the corporate disclosure system with its environment and thus require support in information systems with the technology that led to the system On-Line Real Time that creates rapid data communication and widespread. Optimization of computer-based information system developed by providing opportunities and negative implications of business data in the form of abuse. Shifting Control Methods and Techniques in computer-based information system is essential to the implementation of information systems with the Open Systems. Development of new control techniques required in line with the rapid changes in information technology